A Decade of Scientific Publications on Microbial Biotechnology for Sustainable Agriculture - Judijanto, Loso (Westscience Press, 2025)
The increasing demand for sustainable agricultural practices has driven significant scientific interest in microbial biotechnology over the past decade. This study presents a scientometric analysis of global research on microbial biotechnology for sustainable agriculture from 2014 to 2024, using data retrieved from the Scopus database and analyzed through VOSviewer software. The results reveal major thematic clusters centered around soil health, plant growth-promoting microbes, rhizosphere dynamics, bioremediation, and microbial metabolism. India, China, the United States, and Brazil emerged as leading contributors, supported by strong international collaboration networks. Keyword co-occurrence, institutional collaboration, and country mapping analyses indicate a growing integration of microbial research with broader environmental and sustainability agendas. Furthermore, the study identifies recent shifts in focus toward climate resilience, microbiome-based approaches, and ecological intensification. The findings offer valuable insights for academic researchers, policymakers, and agricultural stakeholders, highlighting both the intellectual development of the field and its practical applications for addressing global agricultural and environmental challenges.